واقع تطبيق آليات حوكمة الشركات في البيئة الجزائرية " مجمع صيدال نموذجا" - يمامي, ساره; نوبلي, نجلاء (جامعة الوادي - University of Eloued, 2024)
لقد جاءت دراستنا بهدف التعرف على واقع تطبيق آليات حوكمة الشركات في الجزائرو تقييمها، وذلك من خلال عرض السياق النظري للدراسة و بعدها عرض حالة مجمع صيدال –الجزائر. ومن أهم النتائج التي توصلت إليها الدراسة أن تطبيق آليات حوكمة الشركات في مجمع صيدال لازال بعيدا كل البعد عن المستوى المطلوب وذلك لغياب إطار قانوني فعال لتطبيقها. ومن أجل تفعيلها لابد من إصدار تشريعات خاصة بحوكمة الشركات مع التطبيق الفعلي لها وإنشاء لجان متخصصة تشرف على متابعة تنفيذها. Our study came with the aim of identifying the reality of the application of corporate governance mechanisms in Algeria , by presenting the theoretical context for the study and then presenting the case of the Saidal Group – Algeria –. One of the most important findings of the study is that the implementation of corporate governance mechanism in the saidal group is still far from the required level due to the absence of an affective legal framework for their implementation. in order to activate it , it must be issued legislation related to corporate governance with its actual implementation and the establishment of specialzed committees to supervise followup implementation.
The reality of the application of corporate governance mechanisms in the Algerian environment "Saidal Complex is a model"
مقال
Keywords: آليات حوكمة الشركات،حكم راشد، تطبيق فعلي، مجمع صيدال.; corporate governance mechanisms, Good governance,actual application,Saidal group.